PRÁTICAS EDUCATIVAS NA PROMOÇÃO DA ALIMENTAÇÃO ADEQUADA E SAUDÁVEL PARA AS PESSOAS COM DOENÇA FALCIFORME - Jorginete de Jesus Damião Trevisani; Marta Citelli dos Reis; Pilar Silva Raphael Mataratzis; Karen Cordovil; Ana Cecilia Freitas; Débora Lemos Lino; Juliana Omena; Cláudia dos Santos Cople-Rodrigues (Universidade do Estado do Rio de Janeiro, 2014)
Sickle Cell Disease (SCD) is a chronic inherited disorder, characterized by the presence of abnormal erythrocytes containing S hemoglobin (HbS) that leads to diverse clinical complications and special nutritional needs. This article aimed to describe food and nutrition education actions for people with SCD. This is a report of the experience with educational practices developed by a Reference Center and performed at a hematology ambulatory in the university hospital from 2010 to 2012 that aimed to promote adequate and healthy eating habits. Data were obtained by consulting the educational practice notes; 171 people participated in 15 educational practices. The subjects were grouped into four main themes: General recommendations for people with sickle cell disease; Increased nutrient requirements; Strategies to reduce salt and sodium intake; and Iron content and availability in foods. Educational practices allowed for the reflection and guidance on appropriate feeding practices and for the findingof doubts on dietary recommendationsfor SCD through people's own reports. The space in the waiting room promoted the exchange of knowledge between the professionals who conducted the practices and participants. However, it was noted as weaknesses, the focus centered on the nutrients, the difficulty of adopting methodological strategies more targeted for age and the lack of inclusion of a multidisciplinary team. The experience presented has important reflections on the need for food, and food and nutrition education is common tool to healthcare professionals throughout the network of assistance to people with sickle cell disease. DOI: http://dx.doi.org/10.12957/demetra.2014.10539